"Sistema web multimedia para la gestión académica de evaluaciones en el instituto de idiomas de la UTEQ" - Rivera Coque, Ana Lucía (2012)
The Instituto de Idiomas (IDI) upon forming part of an accredited institution as the Universidad Técnica Estatal de Quevedo, it is seen in the obligation of being to the vanguard in which to educational technology it refers, helping the educational and students to fortify the knowledge through a middle that nowadays is of common use in the community in general, the Internet. The incorporation of information technology and communication in the classroom has been a change in traditional teaching methodological and attitudinal both for teaching professionals, and for the students. Through the web system will access the student media do their assessments online, getting your score immediately. You will also have access to a system of academic feedback exercises, which feature interactive exercises on scenarios based on the topics covered in class. The system has been developed using the Dynamic Systems Development Methodology Method (DSDM) based on rapid application development (RAD), you can program the system using any application development environment and because the end user is considered as a member of the development team that is given much importance to his opinion. The investigate method based on the hypothesis and the objectives pursued has been the explanatory-experimental because their interest is in explaining why a phenomenon occurs and under what conditions is it, or why two or more variables are related. For hypothesis testing we used Student's t test because it compares the time used in the assessment process both traditional and the optimized and it is assumed that the data correspond to a normal function as the sample is less than 30 people.